Analysis of Medical Waste Management at UPTD Datu Beru Takengon Hospital - Ferawati, Use; Nuraini, Nuraini; Fitria, Aida (PROMOTOR, 2025)
Based on the 2014 Indonesian Health Profile, it is known that nationally there are 74.76% of districts/cities that have implemented medical waste management guidance and have not met the target of the 2014 Ministry of Health Strategic Plan, which is 75%. The number of hospitals in Indonesia is 2,601 hospitals. Hospital medical waste belongs to the category of hazardous and toxic waste that is very important to manage properly. Some medical waste is included in the category of hazardous and infectious waste. There are still many hazardous medical wastes in the form of chemical waste, pharmaceutical waste, heavy metals, genotoxic waste and pressurized containers that have not been properly managed. Meanwhile, infectious waste is waste that can be a source of disease both for hospital human resources, patients, visitors/patient referrals or the community around the hospital environment. Infectious waste is usually in the form of patient body tissues, syringes, blood, bandages, culture cultures, materials or equipment that come into contact with infectious diseases or other media that are estimated to be contaminated by the patient's disease will be the main threat to public health where the UPTD DATU BERU HOSPITAL is close to the settlement allows environmental pollution if waste management is not carried out properly. This study aims to determine the analysis of solid medical waste management in UPTD DATU BERU HOSPITAL. This study uses a type of descriptive research, using qualitative methods. The respondents in this study were in accordance with the above criteria of 2 key informants, 2 main informants and 3 triangulated/additional informants totaling 7 people. The results of this study show that there is still a lack of commitment of hospitals in the solid medical waste management system, supporting facilities have not been fulfilled, and the stages of waste management and labeling have been carried out. The final disposal site is not suitable and needs to change the sanitary landfill method. It is recommended to the hospital to increase commitment to waste management, equip each waste-producing room with needle cutters, safety boxes in each room, equip personal protective equipment, provide immunization programs and health checks.